Development of a Brief Elder Abuse and Neglect Screening Tool for Emergency Medical Services: Detection of Elder Abuse Through Emergency Care Technicians (DETECT), Texas, 2015 - Cannell, M. Brad ([Verlag nicht ermittelbar], 2022)
In collaboration with Texas Adult Protective Services (APS) and one of the largest mobile healthcare providers in North Texas -- MedStarMobile Healthcare (MedStar) -- this study developed and piloted an elder abuse (EA) screening tool: Detection of Elder Abuse Through Emergency Care Technicians (DETECT). The DETECT tool was designed specifically to help medics identify potential EA among community-dwelling older adults during an emergency response. DETECT relies entirely on the medics' systematic observations of the older adults' physical and social environment -- no direct questioning of the older adult or their caregivers is involved. The DETECT tool was developed through an iterative, user-centered design process in which input was gathered from key stakeholders, and revisions to the tool incorporated their feedback. The intent was for that process to result in an EA screening tool that was easy for medics to use in the field and that helped medics capture information about older adults, their environments, and their caregivers that is thought to be associated with the occurrence of EA.